Evaluating the Conformity of Oil Palm Plantation Spatial Utilization with Regional Spatial Planning Policy and Its Institutional Implications in South Barito Regency - Moh Fitrah Rawuh; Hadi Susilo Arifin; Andrea Emma Pravitasari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The expansion of oil palm plantations in South Barito Regency, Central Kalimantan has accelerated significantly from 402.72 ha/year (2011–2014) to 776.70 ha/year (2014–2022), raising serious concerns about the conformity of actual land use with the Regional Spatial Plan (RTRW) 2014–2034 and the biophysical suitability of plantation development sites. This study aims to evaluate the conformity of oil palm plantation spatial utilization with RTRW policy and formulate strategic recommendations for RTRW improvement, with emphasis on institutional implications. A Geographic Information System (GIS) approach was employed, integrating multi-temporal satellite imagery analysis (Sentinel-2, 2014 and 2022), biophysical land suitability assessment using BBSDLP guidelines, spatial conformity analysis through overlay of existing land use maps with RTRW spatial patterns, and a Pentahelix-based SWOT analysis involving five stakeholder groups: Government, Academia, Business, Community, and Media. Results reveal that only 31.02% (4,325.39 ha) of existing plantations are located within conforming zones, while 58.9% (8,217.83 ha) are in non-conforming zones—predominantly overlapping with mining zones (31.51%) and residential zones (27.28%). Land use dynamics show a dramatic 289.40% increase in swampland and a 36.32% decline in shrubland, while plantation area itself decreased by 12.64% despite maintaining 83.53% persistence. Biophysical land suitability assessment reveals that 49.42% of the study area falls under the not suitable (N) class, with rooting media constraints as the primary limiting factor. SWOT-Pentahelix positioning in Quadrant IV (WT) yields five hierarchical strategies for RTRW improvement: ecological restoration, institutional strengthening and permit conflict resolution, RTRW revision based on land suitability, land rehabilitation and transitional zone management, and strengthened monitoring systems. These findings demonstrate significant gaps in spatial planning implementation and inter-sectoral coordination, contributing to the evidence base for evidence-driven spatial policy reform in Indonesia.